Quality of Life Assessment in Patients with Malocclusion Undergoing Orthodontic and Orthognathic Treatment - Vučić Ljiljana; Glišić Branislav; Vučić Uroš; Drulović Jelena; Pekmezović Tatjana (Sciendo, 2020)
The objective of this study was to assess pre-treatment quality of life and the relevant clinical variables in adult patients with malocclusion in order to improve orthodontic treatment strategies.